The model of efficiency prediction and rational choice variants of individual border service “C” mobile groups application during the situation in areas of the state border aggravation - Gorodnov, V. P.; Nazarenko, V. О.; Meiko, О. V. (Honor and Law, 2019)
Justified and presented the model formulary scheme that allows to predict the actions effectiveness and to select parameters of rational variants of individual Border Service “C” mobile groups application during the situation in areas of the state border aggravation.